Propofol EC50 for inducing loss of consciousness in patients under combined epidural-general anesthesia or general anesthesia alone: a randomized double-blind study - Jiangling Wang; Jiangling Wang; Yajian Shen; Yajian Shen; Wenjing Guo; Wen Zhang; Xiaoying Cui; Shunv Cai; Xinzhong Chen (Frontiers in Medicine, 2023)
BackgroundCombined epidural-general anesthesia (GA + EA) has been recommended as a preferred technique for both thoracic and abdominal surgery. The epidural anesthesia on the general anesthetic (GA) requirements has not been well investigated. Therefore, we conducted the present study to explore the predicted effect-site concentration of propofol (Ceprop) required for achieving the loss of consciousness (LOC) in 50% of patients (EC50) with or without epidural anesthesia.MethodsSixty patients scheduled for gastrectomy were randomized into the GA + EA group or GA alone group to receive general anesthesia alone. Ropivacaine 0.375% was used for epidural anesthesia to achieve a sensory level of T4 or above prior to the induction of general anesthesia. The EC50 of predicted Ceprop for LOC was determined by the up–down sequential method. The consumption of anesthetics, emergence time from anesthesia, and postoperative outcomes were also recorded and compared.ResultsThe EC50 of predicted Ceprop for LOC was lower in the GA + EA group than in the GA alone group [2.97 (95% CI: 2.63–3.31) vs. 3.36 (95% CI: 3.19–3.53) μg mL−1, (p = 0.036)]. The consumption of anesthetics was lower in the GA + EA group than in the GA alone group (propofol: 0.11 ± 0.02 vs. 0.13 ± 0.02 mg kg−1 min−1, p = 0.014; remifentanil: 0.08 ± 0.03 vs. 0.14 ± 0.04 μg kg−1 min−1, p < 0.001). The emergence time was shorter in the GA + EA group than in the GA alone group (16.0 vs. 20.5 min, p = 0.013).ConclusionConcomitant epidural anesthesia reduced by 15% the EC50 of predicted Ceprop for LOC, decreased the consumptions of propofol and remifentanil during maintenance of anesthesia, and fastened recovery from anesthesia.Clinical trial registrationClinicalTrials.gov, identifier: NCT05124704.